PUBLIC DANGER AND CURRENT ISSUES OF QUALIFICATION OF VIOLATION OF INVIOLABILITY OF HOUSING - NOVIKOV Valery Anatolyevich (Правовое государство: теория и практика)
The inviolability of housing is the most important constitutional right. Violation of the inviolability of housing entails criminal liability. The crime is classified as a minor offence. However, under certain circumstances, this crime may have a very high degree of public danger. In this regard, the issue of the influence of various factors on the degree of public danger of violating the inviolability of housing is relevant. Purpose: to determine, based on the analysis of criminal legislation and modern judicial practice, the influence of various circumstances on the degree of public danger of violating the inviolability of housing; to interpret the basic concepts used in Article 139 of the Criminal Code of the Russian Federation; to develop recommendations for qualifying the crime; to make proposals for amending the current legislation. Methods: dialectical, comparative legal, logical and legal, systemic interpretation, analysis. Results: the conducted study establishes that the purpose of illegal entry into a home and some of the methods of its commission significantly increase the degree of public danger of the act, and also that the elements of the crime provided for in Article 139 of the Criminal Code of the Russian Federation do not cover all possible types of violation of the inviolability of housing. It is proposed to fill the gap by introducing amendments and additions to the legislation on administrative offences.